Teacher Quality, Modern Technology Applications and Teaching at a South-Western Nigerian University - Adeyanju, Lade (2014)
Increase in enrolment of learners at the different levels of the educational system and particularly in the South-western Nigerian universities motivates this paper. The stretched facilities, infrastructure, poor funding and attitude of stressed teachers to adoption of new technologies affect quality teaching and thus demand the attention of instructional designers. It is felt that the application of modern technologies in teaching and learning, especially the interactive instructional design packages as used in the (K12 school education) would lead to quality teaching. It was suggested that teachers be encouraged to explore the potentials found in the information communication technologies (ICTs).